FAMILY’S EXPERIENCES IN TAKING CARE PATIENTS WITH HALLUCINATION - Sri Eka Wahyuni; Mahnum Lailan Nst; Wardiyah Daulay (Idea Nursing Journal, 2017)
ABSTRACTHallucination is one of positive symtoms that occurred in patient with schizophrenia. It is also the wrong perception experienced by the patients without any stimulus from their surroundings. The perception experiences are real for the patients while others do not experience the same perception with them. This study aims to describe family’s experiences of taking care patients with hallucination. This research took 15 participants. Trust process and approaches were conducted before carrying out an in depth interview. This research was conducted at Mental Health Hospital of Prof. Ildrem Medan. The data were analyzed by using Collaizi’s technique. The results found thats themes: the burden had by the family when taking care of the patients, the impacts of hallucination, the actions taken by the family and the obstacles faced by family while taking care of the patients with hallucination. This research provides the descriptions to all health care providers in taking care person with schizofrenia. Keywords: Hallucinations, experience, family.